SCIENTIFIC AND THEORETICAL APPROACHES TO THE TRAINING OF FUTURE OFFICERS (American Journal of Interdisciplinary Research and Development, 2026)
The article is devoted to highlighting scientific and theoretical approaches in the training of future officers, the role of future officers, their political role in ensuring state security, and other aspects.